Revitalization Strategy of Pasar Pagi through the Relocation of Traders to Segiri Grosir Market, Samarinda - Nadya Putri Afdilla; Andi Nur Pratiwi Fatmala (Universitas Negeri Gorontalo, 2026)
This study examines the strategic management of trader relocation as an integral component of traditional market revitalization, with a case study of Pasar Pagi Samarinda and its temporary relocation to Segiri Grosir Samarinda. Traditional markets play a crucial role in supporting local economic activity and micro-enterprises; however, revitalization policies often generate short-term social and economic challenges, particularly during the relocation phase. This research aims to formulate appropriate revitalization strategies by analyzing internal and external factors influencing the relocation process. The study employs a Mixed Methods approach using a Concurrent Embedded design, in which qualitative data are prioritized through interviews, observations, and document analysis, supported by quantitative weighting and scoring within a SWOT analysis framework. The results of the Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS) indicate that the relocation strategy is positioned in Quadrant I of the SWOT Matrix, reflecting strong internal capacity and favorable external conditions. Key strengths include regulatory support, facility availability, and improved market management, while major challenges involve infrastructure deficiencies, trader adaptation, and declining customer loyalty. The study concludes that a growth-oriented Strength–Opportunity (SO) strategy, complemented by selective defensive measures, is essential to mitigate income decline, enhance trader competitiveness, and ensure the sustainability of traditional market revitalization programs.